Perspektif Sanksi Pidana Kurator Menurut Hukum Kepailitan - Ronald Saija (Postgraduate Program in Law, Universitas Pattimura, 2021)
Introduction: Some bankruptcy cases eventually evolve into criminal matters when a bankruptcy curator who is responsible in handling and administering bankruptcy case is positioned as defendant charged for conducting criminal acts.Purposes of the Research: The purpose of writing is to find out and analyze the perspective of curator criminal sanctions according to bankruptcy law.Methods of the Research: Normative juridical research, namely an approach based on legal materials by examining concepts, legal principles and legislation related to this research.Results of the Research: Criminal sanctions for non-independent curators aimed at preventing the curator from committing criminal acts in the course of the execution of the duty and maintenance tasks. Here, the role of criminal law is as a guardian of the norms that exist in the Law on Bankruptcy related to the duties and responsibilities of the curator. In order for a curator or committee before declaring his willingness to accept the duties and responsibilities of the consequences of the bankruptcy verdict or the postponement of the debt obligation obligation (PKPU) really ensure that he will not commit a disgraceful act of.